Recycling plastic waste in Manaus (AM): The case of waste pickers (Research, Society and Development, 2022)
Despite the National Solid Waste Policy in Brazil being well established, the country reuses very little of its urban solid waste, such as paper, plastic, among others; that is, most of it is dumped in landfills and inappropriate places. In the case of the North region, with an area of ​​45.2 of the Brazilian territory and with the greatest diversity in the world, the recyclables market is still low, mainly in the city of Manaus. Therefore, in this work, the organizations of waste pickers in Manaus that work with recyclable plastic materials were studied in order to show a diagnosis of plastic waste recycling. In this way, a questionnaire containing questions about the functioning process of the collectors' entities was applied. The sample space of this study consisted of seven collectors' entities for an experimental error of 2.5%. The results of this study show that plastic waste is not the main source of income among recyclable materials from waste pickers in Manaus. In addition, the collectors' entities and the government do not exchange information about urban solid waste in the city of Manaus, which makes the recycling process difficult, especially for plastic waste. Considering the total volume of plastic solid waste of 91,080 kg, sold per year, we have a total revenue of R$ 213,072.00/year. Just for plastic waste. The lack of synchronization of information and management between the government and the collectors' entities partly explains the amount of only about 0.27% of urban solid waste being recycled in the city of Manaus. On the other hand, recycling plastic waste is an alternative for reducing greenhouse emissions and can be a source of carbon credits, bringing benefits to the Amazon.